The Encyclopedia of mammals : 2 - Macdonald, David W. (David Whyte) (London : George Allen & Unwin, 1984)
Text and over 800 full-color illustrations detail every living species of mammal.
What is a mammal? -- Carnivores -- Cat family -- Dog family -- Bear family -- Raccoon family -- Weasel family -- Mongoose family -- Hyena family -- Sea mammals -- Whales and dolphins -- Toothed whales -- Baleen whales -- Seals and sea lions -- Sea cows and manatees -- Primates -- Prosimians -- Monkeys -- Apes -- Tree shrews -- Flying lemurs -- Large herbivores-the ungulates -- Primitive ungulates -- Hoofed mammals -- Even-toed ungulates -- Small herbivores -- Rodents -- Squirrel-like rodents -- Mouse-like rodenst -- Cavy-like rodents -- Logomorphs -- Elephant-shrews -- Insect-eaters and marsupials -- Insectivores -- Edentates -- Bats -- Monotremes -- Marsupials.
Includes bibliographical references : (pages [xvi]-xvii) and index.
Keywords: Mammals